Development student worksheets based question, read, reflect, recite, review (PQ4R) to improve creatives thinking skills - Oktri Wulandari; Pujiati Pujiati; Arwin Subakti (Jurnal Prima Edukasia, 2021)
This research and development aims to develop student worksheet based on proper preview, question, read, reflect, recite, review (PQ4R) (valid, practical and effective). This development research uses the Borg Gall design which consists of 10 steps. At this research stage, it only uses 5 steps and is divided into three stages. The first stage is preliminary, at this stage it is used to take initial data and review the curriculum, then in the second stage of planning and development, at this stage it is used to design student worksheet, design student worksheet, and make student worksheet. At this stage the student worksheet product is produced. The third stage is the field test stage, at this stage it is used to test practicality and effectiveness. The population in this study were elementary schools in the Rose Cluster, Kotabumi Kota District, North Lampung Regency. The sample of this research was grade IV Students. Data collection techniques are observation, expert validation sheets, documentation, and questionnaires. The results of research and development, namely student worksheet based on PQ4R are very suitable for use as teaching materials in grade IV learning based on the results of the assessment of material experts 85.5 (very good), media experts 92.0 (very good), language experts 93.3 (very good ), and the practitioner test got an average value of 83.5 (very good). The results of the n-gain test showed that the student worksheet based PQ4R used was effective with a value of 0.47.